Regulatory State and Judicial Decisions in Telecommunications in Mexico - Alvarez, Clara Luz (Law, State and Telecommunications Review, 2018)
Purpose ”“ To assess the role of the judiciary in defining the Regulatory State and in regulating telecommunications in Mexico after almost 5 years of the creation of an independent regulator for telecommunications and broadcasting (Instituto Federal de Telecomunicaciones) with authority in antitrust matters. Methodology/approach/design ”“ To identify the most relevant judicial decisions in telecommunications and antitrust matters, research upon the context in which they were adopted, analyze the content of the decisions and identify the impact of such judicial decisions in the construction of the Mexican Regulatory State, and in the law, in regulation/acts of the regulator. Findings ”“ The main findings are that: (1) the Mexican Regulatory State is a reality now, even if it is in its beginnings; (2) Congress is receptive to Judiciary´s decisions; and (3) deference by judiciary to the regulator is not a blank check, even if there are complex technical issues and a discretionary decision. Practical implications ”“ The identification of a Regulatory State in Mexico evidences that there are deep changes in the traditional relationship between Congress and regulators. Also, the deference granted by the courts to regulators must be considered as a consequence of such Regulatory State. Nonetheless and despite the deference to regulators, Judiciary´s role in building the telecommunications and broadcasting sector is paramount, because judicial decisions ultimately define it. Originality/value ”“ Major changes to telecommunications and broadcasting have taken place in Mexico in the last years. Therefore, there has been scarce research and analysis about the new role of regulators, legislators, and judges, in the so called Regulatory State in Mexico. Moreover, the experience of Mexico may be valuable for other scholars which are assessing public policy in their own Latin American countries or in countries with similarities to them.